N‐glycan in cockroach allergen regulates human basophil function. Issue 4 (20th February 2017) - Do, Danh C.; Yang, Shuang; Yao, Xu; Hamilton, Robert G.; Schroeder, John T.; Gao, Peisong
Abstract: Introduction: Cockroach allergen exposure elicits cockroach sensitization and poses an increased risk for asthma. However, the major components in cockroach allergen and the mechanisms underlying the induction of cockroach allergen‐induced allergy and asthma remain largely elusive. We sought to examine the role of cockroach‐associated glycan in regulating human basophil function. Methods: N‐linked glycans from naturally purified cockroach allergen Bla g 2 were characterized by MALDI‐TOF mass spectrometry. Binding of cockroach allergen to serum IgE from cockroach allergic subjects was determined by solid‐phase binding immunoassays. Role of cockroach associated glycan in histamine release and IL‐4 production from human basophils was examined. Expression of C‐type lectin receptors (CLRs) and their role in mediating glycan‐uptake in the basophils was also investigated. Results: MALDI‐TOF mass spectrometric analysis of N‐glycan from Bla g 2 showed complex hybrid‐types of glycans that terminated with mannose, galactose, and/or N‐acetyl glucosamine (GlcNAc). Deglycosylated Bla g 2 showed reduced binding to IgE and was less capable of inducing histamine release from human basophils. In contrast, N‐glycan derived from Bla g 2 significantly inhibited histamine release and IL‐4 production from basophils passively sensitized with serum from cockroach allergic subjects. An analysis of CLRs revealed the expression of DC‐SIGN and DCIR, but not MRC1 and dectin‐1, in human basophils. Neutralizing antibody to DCIR, but not DC‐SIGN, significantly inhibited Bla g 2 uptake by human basophils. A dose‐dependent bindings of cockroach allergen to DCIR was also observed. Conclusions: These observations indicate a previously unrecognized role for cockroach allergen‐associated glycans in allergen‐induced immune reactions, and DCIR may play a role in mediating the regulation of glycan on basophil function. Abstract : We examined the role of cockroach‐associated glycan in regulating human basophil function. These observations indicate a previously unrecognized role for cockroach associated glycans in allergen‐induced immune reactions, and DCIR may mediate the regulation of glycan on basophil function.